Role of Vitamin D and E as Antioxidants Against Cerebral Endothelial Dysfunction: An In Vivo Study in White Rats (Rattus norvegicus) Sepsis Model - Fajri, Fauzan; Fajar, Sukmawan; Hasan, Denny Irmawati; Dimiati, Herlina; Amna, Eka Yunita; Sovira, Nora; Anidar, Anidar; Safri, Mulya; Gunawan, Aris (Journal of Basic Medical Veterinary, 2024)
Sepsis is a life-threatening condition caused by the body's response to an infection, leading to organ dysfunction. A antioxidants can help neutralize harmful free radicals that cause cellular and tissue damage through oxidative stress. Vitamin D and E are two antioxidants that have been extensively studied for their potential effectiveness. This study aims to evaluate the effectiveness of vitamins D and E in reducing oxidative stress in the cerebral vascular endothelial cells of Wistar mice in a sepsis model. The study follows an experimental design and uses a posttest with a control group. The levels of NO and SOD in 24 sepsis model mice were measured using ELISA, and the cerebral endothelial tissues were examined histopathologically. An ANOVA test was performed, followed by the Post Hoc LSD test. NO and SOD levels decreased in sepsis rats from 66.88 ± 16.59 to 88.77 ± 12.83µmol/L. Sepsis mice given vitamin D and E showed significant results on changes in NO and SOD levels (p<0.05). Based on the histopathological results of necrosis, inflammation, and hemorrhagic cell damage in sepsis rats reached over 50% of the field of view, significantly different from sepsis mice that had been given vitamin D and E. Sepsis mice were given vitamin D and E influenced 96.2% and 98.7% on changes in NO, SOD, and cerebral endothelial dysfunction (p<0.05). These findings imply that vitamins D and E may be beneficial in managing sepsis-induced cerebral endothelial dysfunction, potentially impacting the treatment and outcomes of sepsis patients.